(untitled) (Al Basirah, 2022)
Islam does not limit our life to prayer, fasting, Hajj, Zakat, Jihad, Da’wah, and preaching, but it guides us to follow the path of the Holy Prophet (PBUH) which is a model for all humanity. The bright and ideal aspect of his life is that he not only preached prayers and fasting but also conveyed the message of human rights, He worked and conveyed this message to his Companions for maintaining human rights and the importance of kinship. Living in society is an integral part of the comprehensive concept of goodness that Islam has given to humanity. The survival and security of a nation depend on a pure bond like marriage. Islam has made marriage an important part of the formation of human society. Islamic law has protected the rights, identities, and preferences of the people so that the world order is maintained harmoniously. The spirit of Islam is based on the integration of thought and action, ideology, and practice at individual and communal levels.